POTENTIAL OF FABRICATION OF DURIAN SKIN FIBER BIOCOMPOSITES FOR FOOD PACKAGING APPLICATION THROUGH THE ELECTRICITY IMPACT ANALYSIS - Anuar, Hazleen; Abd Rashid, Siti Munirah Salimah; Mohd. Nordin, Nurfarahin; Ali, Fathilah; Buys, Yose Fachmi; Thomas, Sabu; Mohd Nasir, Nur Aimi; Mohd Asri, Syazeven Effatin Azma (IIUM Engineering Journal, 2021)
As an effort to replace the petroleum-based polymers and reduce waste-related environmental problems, biopolymers are the best candidate due to their renewable, biodegradable and commercially viable. Initiative have been taken by developing durian skin fibre (DSF) reinforced polylactic acid (PLA) biocomposites with the addition of epoxidized palm oil (EPO). PLA/DSF biocomposites were fabricated via extrusion and then injection moulded. The biocomposites were assessed for its life cycle by developing a system boundary related to its fabrication processes using GaBi software. The life cycle assessment (LCA) of PLA/DSF biocomposites show that global warming potential (GWP) and acidification potential (AP) were the major impacts from PLA/DSF biocomposite. For PLA/DSF biocomposite, the results were 199.37 kg CO2 equiv. GWP and 0.58 kg SO2 equiv. AP. Meanwhile, for PLA/DSF/EPO biocomposite, the results obtained were 195.89 kg CO2 equiv. GWP and 0.57 kg SO2 equiv. AP. The GWP and AP were contributed by the electricity used in the fabrication of biocomposites. These impacts were due to the usage of electricity, which contributed to the emission of CO2. However, the PLA/DSF/EPO biocomposite had lower negative impacts because EPO improved the workability and processability of the biocomposite, and hence, reduced the amount of energy required for production. It can be concluded that the plasticized PLA/DSF biocomposite can be a potential biodegradable food packaging material as it has favourable properties and produces no waste. ABSTRAK: Biopolimer adalah terbaik dalam usaha mengganti polimer berasaskan-petroleum dalam mengurang masalah pencemaran-sisa. Ini kerana biopolimer boleh diperbaharui, biodegradasi dan sangat maju secara komersial. Inisiatif telah diambil dengan menghasilkan sabut kulit durian (DSF) bersama biokomposit asid polilaktik (PLA) dengan penambahan minyak kelapa sawit terepoksi (EPO). Biokomposit PLA/DSF direka melalui kaedah pemyemperitan dan acuan suntikan. Biokomposit ini dipantau kitar hidupnya dengan membina sistem sempadan berkaitan proses rekaan menggunakan perisian GaBi. Pengawasan kitar hidup (LCA) biokomposit PLA/DSF menunjukkan potensi pemanasan global (GWP) dan potensi pengasidan (AP) menyebabkan impak terbesar komposit PLA/DSF. Dapatan kajian menunjukkan 199.37 kg CO2 bagi GWP dan 0.58 kg SO2 bagi AP bagi biokomposit PLA/DSF. Sementara itu, dapatan kajian bagi biokomposit PLA/DSF/EPO adalah 195.89 kg CO2 bagi GWP dan 0.57 kg SO2 bagi AP. Kedua-dua GWP dan AP adalah disebabkan oleh penggunaan elektrik dalam proses pembuatan biokomposit. Ini adalah kesan daripada penggunaan elektrik, dan menyumbang kepada pembebasan CO2. Walau bagaimanapun, biokomposit PLA/DSF/EPO mempunyai kurang kesan negatif, kerana EPO telah menambah baik kebolehkerjaan dan kebolehprosesan biokomposit, menyebabkan kurang tenaga yang diperlukan dalam proses pembuatan. Kesimpulannya plastik biokomposit PLA/DSF berpotensi sebagai bahan biodegradasi bagi pembungkus makanan kerana ianya mempunyai ciri-ciri yang diperlukan dan tidak menghasilkan sisa buangan.